Adipose Tissue Hormones as Risk Factors for Cardiovascular Diseases in Patients with Subclinical Hypothyroidism - Peeter J. Mets, Kaie S. Vint, Andres T. Saare (Academic Journal of Clinicians, 2025)
Cardiovascular diseases (CVD) are the leading cause of death worldwide. While in 1900 CVD accounted for less than 10% of deaths, according to WHO data, in 2000 CVD became the leading cause of death. In 1996, 15 million people died from CVD worldwide and experts predict that this figure may reach 25 million by 2020. Elevated levels of atherogenic lipids and low levels of high-density lipoproteins (HDL-C) in the blood serum are among the most important risk factors for the development of atherosclerosis and related complications. Recent research has shown that in Europe, women are much more likely to die from CVD than men (55% women, 43% men) [90]. Coronary heart disease (CHD) is the cause of death in women in 23% of cases, stroke in 18%, and other CVD in 15% of cases, while in men CHD is the cause of death in 12% and stroke in 11% of cases. In addition, women, unlike men, are more likely to have multiple risk factors for CVD, namely visceral obesity, insulin resistance, atherogenic dyslipidemia, and arterial hypertension (AH). Over the last decade, studies have been conducted on the relationship between adiponectin, leptin, and resistin with thyroid hormones and TSH. Despite the numerous functions of adiponectin, leptin, and resistin, all of these hormones have one thing in common: they influence the cardiovascular system to varying degrees. There are numerous studies in this area, but the results are contradictory. High leptin levels are one of the prognostic risk factors for the development of cardiovascular complications [126]. Resistin is directly involved in atherogenesis, being a molecular link between the inflammatory process and atherosclerosis of blood vessels. At the same time, a number of studies have not revealed a relationship between the content of resistin in human serum and insulin sensitivity, body mass index (BMI), blood pressure, or lipid metabolism. The anti-sclerotic effect of adiponectin includes stimulation of endothelial proliferation, inhibition of proliferation and migration of vascular smooth muscle cells, and suppression of expression of adhesion molecules in the endothelium. However, a number of researchers have obtained opposite results. The objective of our study is to assess the content of adiponectin, as well as the blood levels of leptin and resistin in women with Subclinical Hypothyroidism without CVD compared with a comparable control group and to conduct a correlation analysis between the level of adiponectin, leptin, resistin and risk factors for the development of CVD in the study group